Deposit product survey and brand elements of Delta Brac Housing Finance Corporation Ltd. - Rahman, Md. Mahbub-Ur (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.